Canons and Cities: Cathedral Chapters and Their Social Composition in Medieval Portugal - Vilar,Hermínia Vasconcelos (2007)
There has been recently a notable growth in the number of studies written on the nature of cities in the medieval period and, at the same time, a rise in the number of analyses of cathedral clergy, both of which have unquestionably contributed to an advance in our knowledge of these areas. In this context, conclusions centering on the existence of spaces of intersection and influence between urban and ecclesiastic elites are relatively common.One of the main objectives of this study is to identify, in the Portuguese case, the spaces of intersection, influence or differentiation between these elites and to establish trends and chronologies in the social composition of these institutions. For this purpose, use will be made of the data collected in four case studies carried out for the dioceses of Braga, Lamego, Lisbon and Évora between the second half of the 13th century and the first half of the 14th century.This attempt to establish a global and comparative vision will still allow for the identification of several main questions that remain open, namely those relating to the presence of certain social groups inside these cathedral chapters and the importance of ecclesiastic careers for the strategies adopted by some families.